The use of random and sequential exercise and their impact on learning some skills in basketball on a sample of first-stage students in the Department of Physical Education, College of Basic Education / Al-Mustansiriya University (Journal of the College of Basic Education, 2022)
Using both the random and successive exercises and their effect in learning some in basket hall . Aim of the study :-Identifying the effect of both random and successive exercises to learn some skills in basketball by the first grade students .Hypotheses of the study:-1-there are significant differences in using the random exercise to learn the chest-pass skill .2-there are significant differences in using the random exercise to learn the return –pass skill .Fields of the study :-1-4-1 ham on field \the first grade students in sport education department at basic education college \al-mustansiriyah university .1-4-2 terminal field \the duration from 9\10\2006 till 30 \12\2006 .1-4-3 special field\the in terror clubs of basic education college in sport education department ,al-mustansiriyah university .Chapter two :-This chapter is called (there tidal background ) which in clouds of learning skill (the random and the successive exercises ) and the notion of ,skill, besides, the basket hall especially the chest and the return passes .Chapter three :-The researchers adopted the experimental design that consists of two experimental groups (1-2) and each has (30) graders who are taught by using the (successive exercise ) and the other are taught by using the researchers used what is called (equivalent groups ) and the variables were controlled that may affect in eternal and external safety of the experimental design .this chapter in clouds also the pilot study in structional program, the basic experiment procedures of the study ,evil auction the performance level and statistics means .Chapter five :-In the light of the results ,four conclusions have been conducted :1-both the (random and successive ) exercises has an effect in lea ran both the chest and return pass skills in basket ball .2-random exercise has an efficient effect in learning both the chest return bass skills3-random exercise is the in learning both the chest and return pass skill in basket ball .